Game-Based Learning dalam Pembelajaran Ekonomi: Uji Coba Media Ular Tangga Quiz pada Siswa SMA N 1 Merangin Kelas X.1 dan X.3 - Feby Marshanda Harbes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning economics at the senior high school level is often perceived as monotonous because the delivery of material tends to be theoretical and dominated by lecturing. This condition leads to low student participation, particularly in production-related topics that are considered abstract and difficult to understand. This study aims to examine the implementation of the educational game Snakes and Ladders Quiz as a game-based learning medium to enhance the participation and understanding of tenth-grade students in learning production processes, factors of production, and production objectives. This research employed a descriptive approach through a simple classroom action research method during the Field Practice Program (PKL). The research instruments consisted of observation sheets, documentation, and students’ answer results generated through the game. The findings indicate that the Snakes and Ladders Quiz successfully increased student enthusiasm, improved classroom interaction, and enhanced students’ comprehension of production concepts. Students became more active in answering questions, engaging in discussions, and participating in learning activities because the game elements created a more enjoyable and less monotonous learning atmosphere. In conclusion, this game-based medium is effective as an alternative instructional tool for economics learning in senior high schools.